Threads of Memory and Livelihood: The Historical Persistence of Sesek Weaving in Kembang Kerang Daya, East Lombok - M. Paisal Wadi; Badarudin Badarudin; Syahrul Amar (Universitas Hamzanwadi, 2024)
This study examines the historical continuity of sesek woven cloth in Kembang Kerang Daya Village, Aikmel District, East Lombok, and the transformation of its economic, social, and cultural roles. It employs a qualitative descriptive approach and historical method comprising heuristics, source criticism, interpretation, and historiography. Data were collected in June 2024 through observation, documentation, and interviews with ten informants, including women weavers, community and cultural figures, and a village official. The findings show that weaving was historically more than a domestic skill: it marked women’s social maturity, transmitted intergenerational values, and supported Sasak ceremonial life. Over time, sesek shifted from a customary obligation and status marker toward a household livelihood, a sphere of women’s economic agency, a creative-economy product, and a potential cultural-tourism asset. Six recognized motifs—subahnale, sabuk peraban, sri menanti, lonong abang ragi genap, pucuk rebong, and bintangan—encode religious, kinship, fertility, ritual-completeness, and social-status meanings. Its continuity is nevertheless threatened by weak intergenerational transmission, time-intensive production, competition from machine-made textiles, and limited market access. Sustainable safeguarding requires family- and school-based regeneration, stronger weaver organizations, motif documentation, meaning-sensitive product innovation, and cultural tourism that positions weavers as principal knowledge holders and beneficiaries.